PENGARUH LITERASI KEUANGAN DAN KEMAMPUAN MANAJERIAL TERHADAP KINERJA UMKM DI KECAMATAN KRAMAT JATI - Daru Rahayu; Mira Munira; Khalida Utami (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
Micro, Small and Medium Enterprises (MSMEs) are the mainstay of the Indonesian economy because MSMEshave a significant role as one of the drivers of the Indonesian economy in providing a source of income for manypeople and as a workforce absorption in Indonesia. This study aims to determine the effect of financial literacyand managerial skills on the performance of MSMEs in Kramat Jati District, East Jakarta. The method in thisstudy uses a quantitative method with primary data in the form of questionnaires and sampling techniques usingnon-probability sampling. The results of this study indicate that financial literacy and managerial skills both havea significant positive influence on the performance of MSMEs.